Do new matrix formulations improve resin composite resistance to degradation processes? - Andrea Soares Quirino da Silva Fonseca; Katia Maria da Fonseca Gerhardt; Gisele Damiana da Silveira Pereira; Mario Alexandre Coelho Sinhoreti; Luis Felipe Jochims Schneider (Sociedade Brasileira de Pesquisa Odontológica, 2013)
The aim of this study was to determine the degradation resistance of three new formulations-silorane-, Ormocer- and dimer-acid-based materials-and compare them to the traditional dimethacrylate-based materials. One silorane- (Filtek P90, P90), one Ormocer- (Ceram-X, CX), one dimer-acid- (N'Durance, ND) and two dimethacrylate-based (Filtek P60, P60; Tetric Ceram, TC) materials were investigated. Water sorption (Wsp) and solubility (Wsl) were determined after the materials were immersed in water for 28 days. Knoop hardness (KH) was determined before and after 24 h immersion in pure ethanol. The flexural-strength (FS) was determined by the bending test after one-week storage in a dry environment or after one-week immersion in pure ethanol. Data were submitted to analysis of variance (ANOVA) and Tukey's test (95%). The three new formulations showed lower Wsp than the dimethacrylate-based formulation. CX (0.50 ± 0.17%) and ND (0.72 ± 0.19%) exhibited the lowest Wsp, whereas P90 (0.02 ± 0.03%) and P60 (0.04 ± 0.03%) showed the lowest Wsl. All resins showed reduced Knoop hardness number (KHN) after ethanol immersion. P60 presented the lowest decrease in KH value (19 ± 5%). TC (48 ± 3%) and P90 (39 ± 9%) showed the highest KHN decrease after ethanol storage. The FS of CX, ND and TC were affected by ethanol storage. The new formulations did not improve the degradation resistance, as compared with the traditional methacrylate-based materials.